Trypanosoma cruzi-Infected Human Macrophages Shed Proinflammatory Extracellular Vesicles That Enhance Host-Cell Invasion via Toll-Like Receptor 2 - Cronemberger-Andrade, André; Xander, Patrícia; Soares, Rodrigo Pedro; Pessoa, Natália Lima; Campos, Marco Antônio; Ellis, Cameron C.; Grajeda, Brian; Ofir-Birin, Yifat; Almeida, Igor Correia; Regev-Rudzki, Neta; Torrecilhas, Ana Claudia (Frontiers in Cellular and Infection Microbiology, 2020)
Extracellular vesicles (EVs) shed by trypomastigote forms of Trypanosoma cruzi have the ability to interact with host tissues, increase invasion, and modulate the host innate response. In this study, EVs shed from T. cruzi or T.cruzi-infected macrophages were investigated as immunomodulatory agents during the initial steps of infection. Initially, by scanning electron microscopy and nanoparticle tracking analysis, we determined that T. cruzi-infected macrophages released higher numbers of EVs (50-300 nm) as compared to noninfected cells. Using Toll-like-receptor 2 (TLR2)-transfected CHO cells, we observed that pre-incubation of these host cells with parasite-derived EVs resulted in increased the percentage of infected cells. In addition, EVs from parasite or T.cruzi-infected macrophages or not were able to elicit translocation of NF-κB by interacting with TLR2, and as a consequence, EVs alters the gene expression of proinflammatory cytokines (TNF-α, IL-6 and IL-1β), and STAT-1 and STAT-3 signaling pathways. By proteomic analysis, we observed highly significant changes in the protein composition between noninfected and infected host cell-derived EVs, the presence of parasite proteins were found in EVs from infected macrophages. Thus, we observed the potential of EVs derived from T. cruzi during infection to maintain the inflammatory response in the host.